A Teacher Affects Eternity; He Can Never Tell Where His Influence Stops: A Reassessment of the Contributions of Barney Brooks, A Consummate Educator. Issue 3 (15th September 2021) - Merrill, Walter H.
Abstract : Barney Brooks, MD, was the first Professor of Surgery in the newly reconstituted Vanderbilt University School of Medicine in 1925, a position he held until 1951. He was born on the remote plains of Texas and came from obscure beginnings, but through much hard work and determination, he rose to occupy a position of prominence and was a leader in surgery of national scope. Of his major contributions, he considered teaching to be of the utmost importance, and it was for his efforts in teaching that he was most widely known. His reputation as a stern taskmaster was well deserved, but there are other aspects of this most complex man that bear a closer look. An examination of his archived correspondence is revealing, and it shows him to have been a caring and compassionate individual who formed lasting bonds with medical students and residents, members of his faculty, and others. Thus, his life and contributions to surgery and surgical education should be remembered and celebrated. Abstract : Mini-abstract: This retrospective review of the life and accomplishments of Barney Brooks, MD, was accomplished primarily by reviewing archival materials, including his personal correspondence. He was primarily known as a teacher, and this review brings new focus to his teaching of medical students and surgery residents.